2017
DOI: 10.1037/tra0000177
|View full text |Cite
|
Sign up to set email alerts
|

Trauma and psychological distress in Latino citizen children following parental detention and deportation.

Abstract: These findings lend support to a reconsideration and revision of immigration enforcement practices to take into consideration the best interest of Latino citizen children. Trauma-informed assessments and interventions are recommended for this special population. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
116
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(119 citation statements)
references
References 34 publications
(50 reference statements)
3
116
0
Order By: Relevance
“…With as many as half a million parents deported between 2009 and 2013 (Capps et al : v), children of undocumented parents are also likely to live in fear of a parent's deportation and subsequent family separation (Dreby ; Rojas‐Flores et al ; Zayas ). Within the home, legal status may play a role in determining stratified levels of chores, as well as unequal access to healthcare, educational, and travel opportunities (Dreby ; Mangual Figueroa ; Menjívar and Abrego ).…”
Section: Citizenship and Mixed‐status Familiesmentioning
confidence: 99%
See 1 more Smart Citation
“…With as many as half a million parents deported between 2009 and 2013 (Capps et al : v), children of undocumented parents are also likely to live in fear of a parent's deportation and subsequent family separation (Dreby ; Rojas‐Flores et al ; Zayas ). Within the home, legal status may play a role in determining stratified levels of chores, as well as unequal access to healthcare, educational, and travel opportunities (Dreby ; Mangual Figueroa ; Menjívar and Abrego ).…”
Section: Citizenship and Mixed‐status Familiesmentioning
confidence: 99%
“…These cases demonstrate that legal violence—the suffering that is generated, maintained, justified, and normalized by immigration policies (Menjívar and Abrego )—powerfully affects not just undocumented and liminally legal immigrants, but also U.S. citizens in their midst (Rodriguez ). In fact, the record rates of detention and deportation are having a decidedly negative impact on U.S. citizen children's emotional well‐being (Dreby ; Rojas‐Flores et al ), forcing children to navigate life without parents in the United States, on the one hand, or the educational institutions in their parents' home countries (Hamann et al ; Zayas and Bradlee ), on the other . Along with these scholars' findings, my study suggests a need for policy makers to consider additional protections for U.S. citizen members of mixed‐status families, particularly in the development and enforcement of immigration policy.…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…An estimated 4.5 million U.S. citizen children live in families in which one or both parents are undocumented (Pew Hispanic Research Center, ). A growing body of literature has begun to document the link between parental detention and deportation and Latino children's trauma and psychological distress (Allen, Cisneros, & Tellez, ; Brabeck, Lykes, & Hunter, ; Rojas‐Flores et al., ; Zayas, Aguilar‐Gaxiola, Yoon, & Rey, ). This review paper adds to the literature by proposing that the persistent threat of parental deportation and chronic uncertainty regarding familial safety is also harmful to Latino children and youth, especially those living in mixed‐status households, and is experienced by many children as a form of psychological violence.…”
Section: Concluding Remarks and Recommendationsmentioning
confidence: 99%
“…Studies have documented how the absence of parental love and care can adversely impact the long-term well-being and development of children of incarcerated parents (67). Moreover, a growing body of research shows that Adverse Childhood Events, which include justice-system contact or parental incarceration before the age of 18, are associated with poor physical and mental health outcomes in adulthood (68) and other studies suggest that deportation events can be similarly traumatic to children (39,43).…”
Section: Discussionmentioning
confidence: 99%
“…A different 2016 study obtained similar findings when examining post-traumatic stress disorder among 91 Latino U.S. citizen-children from mixedstatus families. The study utilized the UCLA Posttraumatic Stress Disorder Reaction Index and found that children whose parents had been detained or deported experienced significantly more potentially traumatic events than children whose parents were legal permanent residents (43). This study also presented a "parent report" including the results of the Behavior Assessment System for Children−2nd Edition, Parent Rating Scales-Child (BASC-2 PRS-C) and the Trauma Symptom Checklist for Young Children-Spanish Version (TSCYC-SP) and found that children of detained or deported parents experienced a greater degree of certain forms of psychological distress, with those children having more internalizing problems (p = 0.02), higher measures of depression (p = 0.0009) and higher measures of somatization (p = 0.04) than the children of legal permanent residents (43).…”
Section: Introductionmentioning
confidence: 99%